Supporting the Mental Wellbeing of University Students by Building Social Connectedness - Pinto, Shalom (Auckland University of Technology, 2022)
This practice-led research project explored how universities might better support the mental well-being of tertiary students studying in Tāmaki Makaurau (Auckland). Before the COVID-19 pandemic, university students in Aotearoa (New Zealand) experienced moderate levels of psychological distress (New Zealand Union of Students’ Associations 2018). As a result of the ongoing global pandemic, students mental well-being has declined, as 65% experienced low or extremely low levels of well-being (Dodd et al. 2021). A hybrid methodology of Appreciative Inquiry (Ai) and Design Thinking (DT) was utilised to engage students in the design process, gain an understanding of students’ experiences of university services, and generate a design response that addresses students’ unmet needs. The Appreciative Inquiry process is a strength-based model that draws from the science of positive psychology to enhance what already works (Whatworks n.d.). This methodology follows five stages: Define – Discover – Dream – Design – Deliver (Priest et al. 2013). The Design Thinking process is similar to Appreciative Inquiry, encompassing a range of methods, tools and mindsets that have been applied in this project. In the Define stage of the project, assumption mapping, a contextual review, and an investigation of services informed the research design and question. In the Discover stage, semi-structured interviews were conducted with nine students from three major universities in Tāmaki Makaurau to learn about their experiences with university services. Seven primary themes were generated from a thematic analysis of these interviews, and opportunities for change were identified. In the Dream stage, a speculative future scenario was generated to explore what might be in response to these insights and opportunities. The Design stage of this process proposes what should be by presenting a potential service design response. Finally, the last stage, Deliver, aims to produce an events application alongside a recommendations guide to illustrate how AUT can implement these initiatives.